Steroid profiling in male wobbler mouse, a model of Amyotrophic Lateral Sclerosis - Gonzalez Deniselle, Maria Claudia (2016)
The Wobbler mouse is an animal model for human motoneuron diseases, especially amyotrophic lateral sclerosis (ALS), used in the investigation of both pathology and therapeutic treatment. ALS is a fatal neurodegenerative disease, characterized by the selective and progressive death of motoneurons, leading to progressive paralysis. Previous limited studies have reported steroidal hormone dysregulation in Wobbler mouse and in ALS patients, suggesting endocrine dysfunctions which may be involved in the pathogenesis of the disease. In this study, we established a steroid profiling in brain, spinal cord, plasma, adrenal glands, and testes in 2-month-old male Wobbler mice and their littermates by gas chromatography coupled to mass spectrometry. Our results show in Wobbler mice the following: 1) a marked up-regulation of corticosterone levels in adrenal glands, plasma, spinal cord regions (cervical, thoracic, lumbar) and brain; 2) a strong decrease in T levels in the testis, plasma, spinal cord, and brain; and 3) increased levels of progesterone and especially of its reduced metabolites 5α-dihydroprogesterone, allopregnanolone, and 20α-dihydroprogesterone in the brain, spinal cord, and adrenal glands. Furthermore, Wobbler mice showed a hypothalamic-pituitary-gonadal hypoactivity. Interestingly, plasma concentrations of corticosterone and T correlate well with their respective levels in cervical spinal cord in both control and Wobbler mice. T down-regulation is probably the consequence of adrenal hyperactivity, and the up-regulation of progesterone and its reduced metabolites may correspond to an endogenous protective mechanism in response to motoneuron degeneration. Our findings suggest that increased levels of corticosterone and decreased levels of T in plasma could be a signature of motoneuron degeneration.